Gospel figures in art - Zuffi, Stefano, 1961- (Los Angeles : J. Paul Getty Museum, 2003)
In viewing the great works of sacred Western art, many people find difficulty in understanding the stories and identifying the figures portrayed in them. This informative guide decodes these often-mysterious scenes and reveals a vibrant world of images from the Christian tradition for museum visitors, students, and art enthusiasts alike.
The evangelists and their symbols -- Jesus' family -- The birth and childhood of Jesus -- Stories of Saint John the Baptist -- The public life of Jesus -- Miracles and parables -- The passion -- After the ressurection.
Includes bibliographical references and index.
Translated from the Italian.
Keywords: Bible -- Illustrations; Jesus Christ -- Art; Christian art and symbolism; Bible -- Illustrations